Application of land-use simulation to protected area selection for efficient avoidance of biodiversity loss in Canada's western boreal region. (March 2019) - Carlson, Matt; Browne, David; Callaghan, Carolyn
Abstract: Avoided ecological loss is an appropriate measure of conservation effectiveness, but challenging to measure because it requires consideration of counterfactual conditions. Land-use simulation is a well suited but underutilized tool in this regard. As a case study for the application of land-use simulation to assess the impact of protected areas, we present a scenario analysis exploring conservation options in Canada's western boreal forest. The cumulative effect of multiple natural resource sectors, including oil and gas, forestry, and agriculture, have substantially altered the region's ecosystems in recent decades and elevated risk to wildlife. The evolving state of the region is such that managing risks to biodiversity requires consideration of not only today's but also tomorrow's conditions. We simulated the long-term (50-year) outcomes of land use and protection to caribou, fisher, fish, and resource production in each of 104 watersheds in the 693, 345 km 2 study area. Simulated land use caused increased risk to wildlife in response to northwards expansion of resource extraction and expansion of agricultural lands. For each watershed, indicator performance with and without protection were compared to calculate the benefit (avoided ecological loss) and cost (lost opportunity for resource production) of protection. The capacity for protected areas to avoid disturbance varied substantially across watersheds, as did the potential loss of economic opportunity. Focusing protection on cost-effective watersheds made protected area expansion a more efficient strategy for reducing wildlife risk than reducing the overall rate of natural resource production. Heterogeneity in the cost-effectiveness of protection presents an opportunity to balance ecological integrity and economic growth.